Evaluasi Kandungan Nutrisi Pakan dan Daya Hambat Tepung Biji Asam Kandis (Gracinia cowa) sebagai Bahan Pakan Unggas - Febri Puska Padang; Osfar Sjofjan; Edhy Sudjarwo (Universitas Halu Oleo, 2018)
Kandis acid (Gracinia cowa) has been used for cooking, medicine, beauty, etc., but using of seeds has not been profitable so it was wasted. Seeds can be used as a fitobiotic to replace antibiotics or as feed ingredients. The purpose of this study was to determine the food ingredient and the inhibitory of bacteria on kandis seeds flour. This research was conducted by laboratory experiments using Kandis seeds flour as a material, analysis proximate used to represent the composition of feedstuft, bioactive used test flavonoid quantitaf seconder and the inhibitory test with hollow diffusion methode. The results of the test were dry matter 89.11%, crude fat 4.77, fiber 18.57, crude protein 0.99, tannin 0.29%, GE 5244 kcal / kg, Ca 0.72%, P 0, 22%, flavonoids 0.44%, density 413 g / mL. The smallest inhibitory bacteria produced by lactic acid bacteria then Salmonella and Escherichia coli. The food ingredient represented that value Kandis acid seeds flour can be used as food and there are bacterial inhibitory by the activity of flavonoids and tannins. The conclusion is the kandis acid seeds have potential as feed ingredients and phytobiotics Keywords: gracinia cowa, flavonoid, proximate analysis, inhibition